Preparation of QDs@SiO2-PEG-LMPET and its influence on crystallization and luminescence of polyethylene terephthalate. (12th March 2021) - Wang, Yanqi; Wang, Yao; Zhang, Miaorong; Liu, Jixian; Huang, Linjun; Wang, Yanxin; Hao, Tian; Li, Jie; Tang, Jianguo
Abstract: The composite particles composed of quantum dots coated with silica and grafted with copolymer of polyethylene glycol and low molecular weight polyethylene terephthalate (QDs@SiO2 -PEG-LMPET) are synthesized. The internal QDs provide luminescent performance and combine with SiO2 to form QDs@SiO2 with good dispersion to solve the defect that small-sized SiO2 is prone to agglomerate. The block polymer LMPET-PEG grafted on the surface can make the composite particles better compatible with the PET matrix. In summary, QDs@SiO2 -PEG-LMPET not only play the same role as SiO2 to enhance the crystallization performance of PET matrix, but also provide stable luminescence performance, which is multifunctional additive with broad application prospects.